Groups St. Andrews 2017 in Birmingham - Campbell, C. M. 1942-; Parker, Christopher, 1961-; Quick, M. R.; Robertson, E. F.; Roney-Dougal, Colva Mary (London Mathematical Society lecture note series, 2017)
Every four years leading researchers gather to survey the latest developments in all aspects of group theory. Initially held in St Andrews, these meetings have become the premier forum for group theory across the whole of the UK. Since 1981, the proceedings of 'Groups St Andrews' have provided a regular snapshot of the state-of-the-art in group theory and helped to shape the direction of research in the field. This volume contains papers from the 2017 meeting held in Birmingham. It includes expository articles from the invited speakers, and further surveys contributed by the participants. Topics include: generation of finite simple groups, block theory, fusion systems, algebraic groups, one-relator groups, geometric group theory, and Beauville groups.